2009
DOI: 10.17221/61/2009-pse
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhiza has a direct effect on reactive oxygen metabolism of drought-stressed citrus

Abstract: A greenhouse experiment was conducted to investigate the dynamic trend of symbiotic development in Citrus sinensis/Poncirus trifoliata trees colonized by Glomus versiforme during 12-day lasting drought and to evaluate correlation between symbiotic development and reactive oxygen metabolism of citrus. One year after planting, water was withheld from all trees for 12 days. During the drought stress mycorrhizal colonization and arbuscles showed a durative reduction. Mycorrhizal trees maintained significantly lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 18 publications
3
28
0
3
Order By: Relevance
“…This is consistent with the findings of Wu and Zou (2009), who reported that mycorrhizal grafted citrus seedlings had significantly lower H 2 O 2 and O 2…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with the findings of Wu and Zou (2009), who reported that mycorrhizal grafted citrus seedlings had significantly lower H 2 O 2 and O 2…”
Section: Discussionsupporting
confidence: 93%
“…The amelioration of stress resistance by AM symbiosis is often related to the enhancement of antioxidant levels or activities in plants (Wu et al 2006a, b;Wu and Zou 2009;Ruiz-Sánchez et al 2010;Baslam and Goicoechea 2012). RuizSánchez et al (2010) found that AM symbiosis ameliorated the response of plants to drought by improving photosynthetic performance but mainly through the accumulation of the antioxidant compound glutathione, which was concomitant with a reduction in oxidative damage to membrane lipids and to low cellular levels of hydrogen peroxide.…”
Section: Protection Against Oxidative Stress: Antioxidant Metabolitesmentioning
confidence: 99%
“…Thus, AM J. curcas plants could be accumulating these antioxidant compounds under cold stress to prevent lipid peroxidation. These compounds were not measured in this study, but a higher accumulation in AM plants subjected to drought stress has been reported in several plant species (Wu & Zou, 2009;Ruiz-Sánchez et al, 2011;Baslam et al, 2012). Moreover, a recent study has shown that the benefits of AM symbiosis not only rely in a lower oxidative stress in the host plant, but also restrict locally such oxidative stress, avoiding a systemic damage and allowing the plants to continue with their physiological processes (Bárzana et al, 2015).…”
Section: Discussionmentioning
confidence: 67%